Big Challenges and Big Opportunities: The Power of ‘Big Ideas’ to Change Curriculum and the Culture of Teacher Planning - Hurst, Chris (MEGRA Inc, 2014)
Mathematical knowledge of pre-service teachers is currently ‘under the microscope’ and thesubject of research. This paper proposes a different approach to teacher content knowledgebased on the ‘big ideas’ of mathematics and the connections that exist within and betweenthem. It is suggested that these ‘big ideas’ should form the basis of teacher planning but it isacknowledged that this represents a ‘cultural change’. The proposal is supported by resultsfrom a project that involved pre-service teachers in their final mathematics education unit.Results suggest that a focus on the ‘big ideas’ of mathematics has the potential to changeteacher planning and enhance content knowledge.